Form, Consistency and Relevance of Dhabt in Qur’an Manuscript at Museum of Sunan Drajat Lamongan East Java - Isyroqotun Nashoiha; Romlah Widayati (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2022)
The research was motivated by the development of ancient archipelago manuscripts which had not been widely enjoyed by academic reviewers. One of them is Qur’an Manuscript of Lamongan. This assumption is motivated by a statement stating that the Al-Qur’an in the archipelago has content in terms of text, namely written and in the same shape. The existence of Qur’an Manuscript manuscripts is not a problem and it is not even functioning. The primary data source uses Qur’an Manuscript manuscripts in the Sunan Drajat Lamongan Museum, and several other secondary sources that are related with the issue of the Mushaf and dhabt Al-Qur`an. Meanwhile, the data analysis method used is the structural analysis method, which describes and explains aspects of the work that produce comprehensive works. The results of this study show that the archaic archipelago manuscripts have similarities with the Indonesian Standard Mushaf from various aspects such as the affixing the punctuation of hamzah washal and hamzah qatha ‘, which are included in the breadfruit sign in the reading of izhar, idgham, ikhfa, iqlab in nun sakinah. Meanwhile, other punctuation marks have changed. The use of dhabt in Qur’an Manuscript Lamongan manuscripts from beginning to end experiences consistency, that is, the punctuation in the mushaf does not change shape. The existence of this ancient manuscript has several implications including: implications for the way of the Al-Qur’an, implications for interpretation, and implications that are informative. Such conditions are compiled from data generated from several well documented documentation. Meanwhile, if it is viewed from relevance, there is an inequality between Qur’an Manuscript Lamongan manuscripts and the Indonesian Standard Mushaf in the form of dots, i’rab (harakat rafa’, nashab, jar or jazem), naqish (less) or ziyadah (added) letters, tabdil (replacement letters or words), etc. So that it can force relevance will cause damage to the meaning in the reading of the Al-Qur`an.